Matriarchs of Malabar: A Cultural Study of The Matrilineal Legacy of The Muslim Community In Kuttichira - Semiya P. M; Sukesh Kumaradas (Program Studi Sejarah Peradaban Islam Institut Agama Islam Darullughah Wadda'wah, 2026)
Kuttichira is a historically significant area in Calicut, Kerala. It is known for its unique cultural identity and the practice of matrilineality, in which family lineage and property are traced through women. This study investigates the origins, characteristics, and transformations of the matrilineal system among the Muslim community in Kuttichira. Using qualitative and anthropological methods, including six interviews with inhabitants and researchers of the specific area, as well as archival research in local records, this research examines family structures, gender roles, property management, and the leadership functions of the eldest female in the family. She is locally known as the Karanothi. The study also analyzes the influence of architectural design and patterns in traditional joint-family homes on social organization. The findings reveal that matrilineal and matrilocal systems historically conferred authority and responsibility upon women. She played a central role in family welfare, education, and health, while husbands had limited property rights. These practices varied across each Tharawad. Over time, modernization, socio-economic changes, and legal reforms have transformed these traditions, leading to altered inheritance patterns and family dynamics. This study contributes to an understanding of the historical and cultural evolution of matrilineal practices within Kerala’s Muslim communities and highlights the impact of female-centered family structures on social organization.